Restricting Glutamine Uptake Enhances NSCLC Sensitivity to Third-Generation EGFR-TKI Almonertinib - Liu, Yaming; Ge, Xianming; Pang, Jinlong; Zhang, Yuhan; Zhang, Hao; Wu, Hongyan; Fan, Fangtian; Liu, Hao (Frontiers in Pharmacology, 2021)
Abstract：The emergence of secondary resistance is the main failure cause of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) as a targeted therapy for non-small cell lung cancer (NSCLC). EGFR mutations of NSCLC cells can markedly increase glutamine transporter (SLC1A5) expression, thereby increasing glutamine metabolism. Glutamine metabolites can activate EGFR downstream signals, including mTOR, ERK1/2, STAT3, etc., which is an important cause for the decreased sensitivity of NSCLC to EGFR-TKIs. CCK8 and Annexin V/PI assays were conducted to detect the effects of Almonertinib and/or V9302 on the proliferation and apoptosis of NSCLC cells. Proteomics was used to determine the effect of Almonertinib on energy metabolism-related proteins in NSCLC. siRNA transfection was performed to study the effect of SLC1A5 down-regulation on cell proliferation. In addition, the effects of drugs on colony formation capacity were determined by colony formation assay. Immunofluorescence and Western blot were utilized to detect the apoptosis- and autophagy-related proteins expression. DAPI staining was utilized to detect the effect of drugs on the nucleus. Transmission electron microscope was used to observe the changes of submicroscopic structure such as autophagosomes and nucleus of cells. mCherry-GFP-LC3B tandem fluorescent protein was to used to detect the level of autophagy flux. Tumor-bearing nude mouse model was utilized to detect the effect of V9302 on the anti-tumor effect of Almonertinib in vivo. As a result, Almonertinib suppressed H1975 and A549 cell proliferation depended on its dosage and treatment duration, and it also induced apoptosis. A549 cells with wild-type EGFR had lower sensitivity to Almonertinib. The expression of SLC1A5 was up-regulated by stimulating with low concentration of Almonertinib in NSCLC cells. SLC1A5 was highly expressed in A549 cells with wild-type EGFR. Glutamine deletion or SLC1A5 inhibition/silencing inhibited the proliferation of NSCLC cells, and decreased cellular glutamine uptake. The combination of SLC1A5 inhibitor V9302 and Almonertinib had a synergistic inhibitory effect on the proliferation of NSCLC. V9302 enhanced the effect of Almonertinib in apoptosis-inducing in NSCLC cells. The combination of V9302 and Almonertinib might induce apoptosis by inhibiting autophagy.